Effect of N, P, K, and Mg application on yield and fruit Quality of mandarin (Citrus reticulata) (Bangladesh Journal of Agricultural Research, 2013)
The study was carried out at the farmer's field of Juri Upazilla, Maulavibazar District during 2008-2009, 2009-2010, and 2011-2012 to find out the proper combination of fertilizer nutrients that promotes better fruit yield and quality of mandarin (cv. Khashi Kamla). The treatments were Native nutrient i.e., control (TI), N150P50K150Mg30 (T2), N200P75K175Mg40 (T3), N250P100 K200Mg50 (T4), N300P125K225Mg60 (T5), and N200P75K175Mg0 (T6) g/plant/year. In addition, 20 kg cowdung/plant was used as blanket dose. Yield components, yield, and TSS content (%) of mandarin varied significantly due to variation of nutrients in all the test years. Fruit yield/plant was improved significantly with increase in NPK and Mg dose irrespective of years. Application of Mg in combination with NPK increased 17-157% mean fruit yield over magnesium control. Significantly the highest yield and yield attributes were recorded under treatment N300 P125 K225 Mg60 g/plant (T5) along with 20 kg cowdung/plant in all the years. Total soluble sugar (%) content was also maximum in trees receiving N300P125K225Mg30 g/plant. The highest gross margin and marginal rate of return were achieved by the same treatment (T5). The lowest fruit yield/plant was obtained from untreated control plot (native nutrient). Three years study revealed that application of N300P125K225Mg60 along with 20 kg cowdung/plant would be economically optimum for achieving higher yield and better fruit quality in mandarin grown under piedmont plain soil. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16969 Bangladesh J. Agril. Res. 38(3): 425-433, September 2013